Integration of International Criminal Law Principles in the Regulation of Terrorism in Indonesia A Study of Criminal Law Reform - Nurul Fatimatus Sholihah; Sapto Budoyo; Istiqomah Istiqomah (Yayasan Adra Karima Hubbi, 2026)
Background. This article examines the integration of international criminal law principles into the revision of Indonesia's Anti-Terrorism Law. Purpose. Although Indonesia has updated its anti-terrorism framework with Law No. 5 of 2018 and the new Criminal Code (KUHP 2023), several challenges remain in aligning national legislation with international standards. Method. Through normative and comparative legal methods, this research analyzes relevant international legal instruments, including UN resolutions and conventions on counter-terrorism, and compares them with Indonesian regulations. Results. The findings reveal that Indonesia must further harmonize its anti-terrorism laws to ensure effective law enforcement while protecting human rights. The study provides recommendations to strengthen Indonesia’s legal framework on terrorism. Conclusion. This study concludes that while Indonesia has made significant progress in reforming its anti-terrorism legislation, substantial normative and institutional adjustments are still required to fully comply with international criminal law standards. Harmonization efforts should prioritize clearer legal definitions, proportional enforcement mechanisms, and stronger human rights safeguards to prevent potential abuses of power.